Towards a Society of Merit and Competition. Henry Jones’ Critique of Edwardian Britain - Alessandro Dividus (Scienza & Politica, 2025)
The significant cultural shifts that unfolded in Great Britain during the latter part of the 19th century wrought profound alterations to the nation’s political and social fabric. Henry Jones, albeit regarded as a minor figure within the British idealist movement, offers a meticulous analysis of these transformations, particularly with regard to the emergence and evolution of concepts such as meritocracy, competition, and civic engagement. His discerning observations partially foreshadow themes that would only enter into the political discourse from the latter half of the 20th century onward.